Blood of the provinces the Roman auxilia and the making of provincial society from Augustus to the Severans - Haynes, Ian 1967- (Oxford Univ Press, 2014)
This is the first fully comprehensive study of the auxilia, a non-citizen force which constituted more than half of Rome's celebrated armies. Diverse in origins, character, and culture they played an essential role in building the empire, sustaining the unequal peace celebrated as the pax Romana, and enacting the emperor's writ